Answer:
-6.772001873
Step-by-step explanation:
state that quadratic formula and substitute the terms into it to solve for the answer
Answer:
x1=-6.772
x2=1.772
Step-by-step explanation:
-x²-5x+12=0
For the general quadratic form: ax²+bx+c=0, the roots are found with formula:
x1,2=(-b +- sqrt(delta))/(2a)
where delta=b²-4ac.
In our case: a=-1, b=-5, c=12
delta=b²-4ac=(-5)²-4(-1)×12=25+48=73
Sqrt(delta)=sqrt(73)=8.544
x1,2=(5 +- 8.544)/(-2)
x1=-(5+8.544)/2=-13.544/2=-6.772
x2=-(5-8.544)/2=3.544/2=1.772